1823 Ohio Acts, at 55, 57-58, ch. 38, § 10 (vol. 22, 1824) - (:unkn) unknown (General Publisher, 1823)
to impose a fine of not more than five dollars, for shooting a gun or running a horse within said town, to adopt such regulations as may by them be deemed necessary to secure the town against injuries by fire..."
--
Keywords: DISCHARGE